Role and importance of Scottish Highland Cattle in the world - Kosztolányiné Szentléleki, Andrea; Vertséné Zándoki, Rita; Tőzsér, János; Stefler, József (Animal welfare, Ethology and Housing Systems (AWETH), 2021)
The aim of the study is to introduce history, distribution, appearance, production traits and breeding organizations of Scottish Highland cattle breed. This breed is one of the most ancient cattle breeds and was evolved under very extreme environmental circumstances in the Western part of Scotland, on the Scottish Highland and the offshore Hebrides.Although Scottish Highland cattle is a small sized breed, in favourable cases bulls can weigh even 800 kg, while weight of cows can reach 500 kg. The breed has several excellent traits: it can tolerate extreme geographic and weather conditions, has great resistance to diseases, outstanding grazing and maternal traits. Despite being spread all over the world, the size of the population is relatively small, counts around 50.000 heads. Originally, the breed was selected for beef production (lean, well marbled meat with low cholesterol content), however in Europe it is used in crossbreeding programs, in landscape and environment preservation and agrotourism.
Keywords: ancient cattle breed; crossbreeding partner; foraging behaviour; marbling of beef; cholesterol content of beef; natural vegetation preservation; agrotourism